Perlindungan Merek Dalam Pengembangan Usaha Kecil dan Menengah Bidang Ekonomi Kreatif di Indonesia - Bafadhal, Faizah; Alissa, Evalina; Suhermi, Suhermi (Universitas Jambi, Fakultas Hukum, 2024)
Indonesia is currently experiencing rapid development in the creative economy sector. Various industries such as design, fashion, art, music, film, and others have become the backbone of creative economic growth in this country. One of the most valuable assets in the creative economy is a brand. Brand protection is very important to ensure the continued growth of Indonesia's creative economy. This research aims to determine and analyze the importance of trademark registration in the development of small and medium enterprises in the creative economy of Indonesia and trademark protection in the development of small and medium enterprises in the creative economy. The research results show the importance of registering a trademark, including: To obtain legal protection, exclusive rights to use the trademark, as a publicity tool (promotion), and also as a business opportunity. Brand protection in the development of micro, small, and medium enterprises in the creative economy sector in Indonesia can be done in two ways, namely preventive protection and repressive protection.